Transpiration response to soil drying versus increasing vapor pressure deficit in crops: physical and physiological mechanisms and key plant traits - Koehler, Tina; Wankmüller, Fabian J P; Sadok, Walid; Carminati, Andrea (Journal of experimental botany, 2023)
Abstract The water deficit experienced by crops is a function of atmospheric water demand (vapor pressure deficit) and soil water supply over the whole crop cycle. We summarize typical transpiration response patterns to soil and atmospheric drying and the sensitivity to plant hydraulic traits. We explain the transpiration response patterns using a soil–plant hydraulic framework. In both cases of drying, stomatal closure is triggered by limitations in soil–plant hydraulic conductance. However, traits impacting the transpiration response differ between the two drying processes and act at different time scales. A low plant hydraulic conductance triggers an earlier restriction in transpiration during increasing vapor pressure deficit. During soil drying, the impact of the plant hydraulic conductance is less obvious. It is rather a decrease in the belowground hydraulic conductance (related to soil hydraulic properties and root length density) that is involved in transpiration down-regulation. The transpiration response to increasing vapor pressure deficit has a daily time scale. In the case of soil drying, it acts on a seasonal scale. Varieties that are conservative in water use on a daily scale may not be conservative over longer time scales (e.g. during soil drying). This potential independence of strategies needs to be considered in environment-specific breeding for yield-based drought tolerance. A review explaining the link between soil–plant hydraulics and water use regulation during soil and atmospheric drying.